A new species of the genus Dahira Moore (Lepidoptera: Sphingidae) fromSichuan, China - Jiang, Zhuo-Heng; Wang, Cheng-Bin (Zootaxa, 2020)
A new species of hawkmoth, Dahira sichuanica sp. nov. (Lepidoptera, Sphingidae, Macroglossinae, Macroglossini), is described based on a single male from an evergreen broad-leaf forest in Dafengding Nature Reserve, Leshan, Sichuan, China. The habitus and diagnostic features of the new species are described and illustrated. A list of all Dahira species presently known from China and the distribution map of the new species are also given.